Creativity in the Plague: From Creative Productivity to Retreat - Szmidt, Krzysztof J.; Modrzejewska-Świgulska, Monika (Kultura i twórczość w czasach zarazy: Doświadczenie pandemii a aktywność artystyczna z punktu widzenia twórcy i odbiorcy, 2021)
The authors describe the different attitudes of amateur and professional creators in the face of the coronavirus pandemic and limitations related to the compulsion of social isolation. Taking into account the three main attitudes towards life, described in social pedagogy and pedagogy of creativity: active attitude – creative, passive and escape, in the first part they provide examples of artists’ behavior characteristic of a creative attitude, mainly musicians. The second part describes the case of a group of amateur artists from “Pracownia 413”, run at the Łódź Cultural Center by the visual artist Jacek Świgulski. The behaviors of many amateurs during forced isolation described in this section illustrate passive or “withdrawn” attitudes. The authors try to theorize the manifestations of creativity typical of both types of attitudes and raise several questions for future research on creativity in times of crisis. The text is imbued with the idea – the authors’ conviction that in the times of the plague, creativity did not die, but at most “got sick”.